Achieving Green AI with Energy-Efficient Deep Learning Using Neuromorphic Computing. - TAO LUO; WENG-FAI WONG; SIOW MONG GOH, RICK; ANH TUAN DO; ZHIXIAN CHEN; HAIZHOU LI; WENYU JIANG; WEIYUN YAU (Communications of the ACM, 2023)
This article details a neuromorphic computing projects program in Singapore, a collaboration between the Agency for Science, Technology and Research, A*STAR, and the National University of Singapore (NUS). The ultimate goal of the program is attainment of energy-efficient deep learning practices. Topics include a description of all areas of the neuromorphic computing program with a look at the hardware, middleware, software and system integration implementation.